Older adults' activity destinations before and during COVID-19 restrictions: From a variety of activities to mostly physical exercise close to home. (March 2021) - Portegijs, Erja; Keskinen, Kirsi E.; Tuomola, Essi-Mari; Hinrichs, Timo; Saajanaho, Milla; Rantanen, Taina
Abstract: The aim was to study various types of older adult's activity destinations (counts, frequency of visitation, and distance from home) in the pre-COVID-19 era, and to study prospectively how COVID-19-related regulations limiting mobility affected these. Using a map-based questionnaire, 75-85-year-old participants reported activity destinations, that is, any destinations for physical exercise, destinations facilitating one's outdoor mobility, and destinations for other activities, which they had visited several times during the past month. At baseline, a variety of activity destinations was reported, but during COVID-19, destinations reported markedly declined in number, they were reported predominantly for physical exercise, and they were located closer to home. Highlights: Older adults reported a variety of activity destinations pre-COVID-19. During COVID-19, fewer activity destinations were reported and mostly closer to home. During COVID-19, activity destinations were reported mostly for physical exercise. Map-based questionnaires are meaningful for studying activity behavior in old age. In future, use of map-based study methods will become increasingly relevant.